A Framework of Media Architecture Elements in Redefining Urban Environments - A.NAGARAJAN, VITHYASRE; Abdul Razak, Asrul Sani; Che Din, Nazli (International Journal of Property Sciences (E-ISSN: 2229-8568), 2025)
Media architecture integrates media technology with the built environment, transforming structures into communicative surfaces through digital displays, interactive installations, and dynamic lighting. Despite its innovative nature, research on media architecture's impact on human behaviour and urban experiences remains limited. Lacking unified design principles, this study aims to identify key elements of media architecture and assess their influence on user experience. The study recognizes the absence of standardization and regulations and thus explores how identified elements can lead to innovative, functional designs integrating digital media with physical environments. Proposed conceptual framework was initially tested through case studies of two internationally recognized buildings. Addressing the limited research on media architecture within Malaysia, the framework was then applied to Pavilion Kuala Lumpur. Findings reveal the framework's utility in assessing the integration of built form and digital information, the socio-spatial impact of media architecture, and the balance between commercial and community-oriented content. The study underscores the importance of harmonizing design with context to promote engagement and enrich urban experiences.